Colonoscopy Screening Information Preferences Among Urban Hispanics - Ellison, Jennie (J Immigr Minor Health, 2011)
Existing disparities are evident in colorectal cancer (CRC) screening. We sought to assess preferred sources of colonoscopy screening information among Hispanics in East Harlem, NY. Face-to-face interviews were conducted among average-risk for CRC, non-symptomatic Hispanics in community-based sites and health clinics. SPSS 16 analysis explored the relationships between sociodemographic and health care variables and preferred sources of colonoscopy information for 395 participants. The top four preferred information sources were doctor/ provider, brochures, television, and from someone who speaks the same language. We found significant differences in preferred information sources by a Chi-Square analysis of age (50–64 years; 65 or older), education (0–8th grade; 9th or above), language preferred (English; Spanish), and origin (US-born; foreign-born). Using the identified preferences for sources of information among this growing segment of the US population could inform interventions to address the important public health issue of CRC disparities.